Distribution of microRNA profiles in pre-clinical and clinical forms of murine and human prion disease - Lesley Cheng (Nature Portfolio, 2021)
Cheng et al. present differentially expressed extracellular vesicle miRNAs in human clinical samples from patients who suffer from sporadic Creutzfeldt-Jakob disease. This study identifies biomarkers that can be used to detect prion-related diseases, providing insights into drug development for inhibiting prion infectivity.